Intercultural higher education for indigenous Yucatec Maya in Mexico - Rosado-May, Francisco Javier (2017)
This work presents important decisions made during the implementationof the intercultural educational model at the UniversidadIntercultural Maya de Quintana Roo, Mexico, in a context of povertyand conditions of lagging behind the rest of the society of theindigenous Yucatec Maya population. Within the legal frameworkof public universities in Mexico, the financing of projects, thedeveloping of intercultural pedagogy and designing the institutionalsettings, rested on elements that included learning/transmission andconstruction/innovation of knowledge that combined aspects of thelocal culture with conventional education. High figures on indicatorssuch as retention, graduation rate, employability, and quality ofthe academic programs, along with opinions from alumni, achievedduring the period of February 2007 to February 2015, indicate thatthe decisions and actions taken in the beginning of the constructionof the intercultural model at UIMQRoo, were in the right direction.